An Integrated SVM-LSTM Method for VPP Resource Classification and Load Forecasting in Real-time Market Trading - He Zhao; Yucheng Hou; Zhifa Lin; Xin Cao; Xiao Yu (Journal of Computing and Information Technology)
The operation of virtual power plants in the electricity market requires handling complex resource scheduling and market trading decision-making problems. The research aims to enhance the participation efficiency and responsiveness of virtual power plants in the electricity market and solve practical operational challenges by improving market trading strategies. Therefore, a resource grading model based on improved support vector machine was developed. The model is optimized using adaptive synthetic sampling, principal component analysis, and deep clustering algorithms. In addition, an improved long short-term memory network is utilized to achieve ultra short-term load forecasting. The results showed that the recall rate and F1 mean of the resource grading model based on the improved support vector machine algorithm were as high as 81.07% and 85.41%, respectively. The average prediction error of the improved long short-term memory neural network algorithm is 0.35%, and the maximum error is only 0.62%. In the basic scenario, the maximum deviation between the declared amount of backup auxiliary services based on load adjustable capacity prediction and the actual amount is only 88.62 kW. The method proposed by the research institute has significant advantages in improving the efficiency and responsiveness of virtual power plant market participation, which is conducive to promoting the overall economic benefits of virtual power plants in the electricity market.